Energy consumption pattern and renewable energy alternatives in Madi Kalyanpur, Chitwan, Nepal - Poudel, Sumitra; Chaulagain, Narayan Prassad; Aryal, Manoj (Nepal Journal of Environmental Science, 2016)
Energy consumption pattern and greenhouse gases emission are interrelated. The unsustainable use of biomass and widespread use of commercial energy are of the major sources of greenhouse gas emission. The alternative to kerosene for lighting is solar home system (SHS), which is one of the potential renewable technologies for rural electrification. The present study has analyzed household energy consumption pattern and greenhouse gases emission from energy consumption practices as well as environmental and economic benefits of SHS in Madi Kalyanpur Village Development Committee of Chitwan district. For the purpose, the primary data were collected through household questionnaire survey, key informant interview (KII) and focus group discussion (FGD). The analysis has shown that 22% of household use all types of energy, i.e. fuel-wood, LPG (liquefied petroleum gas), biogas and SHS as the sources of energy. Thirty-five percent households use fuel-wood, LPG and SHS, 24% use fuel-wood, biogas and SHS, 1% used LPG and SHS, 5% use biogas and SHS, 4% use LPG, biogas and SHS and 9% use fuel-wood and SHS as a source of energy. Almost all people have been using SHS for the lighting purpose. The average annual greenhouse gases emission per household from fuel-wood and liquefied petroleum gas consumption was 7.89 ton and 0.17 ton of CO2 equivalent respectively. Typically, a 40 Wp SHS reduced the consumption of kerosene by 42 liter annually for lighting that displaced 0.11 ton of CO2 equivalent per household per year. The simple payback period for typically 40 Wp SHS was found to be nine years with no subsidy, seven years with subsidy from Alternative Energy Promotion Centre and two years with Indian Government Grant. Similarly, the benefit-cost ratios were found to be 3.1, 3.5 and 4.6 for the systems with no subsidy, with AEPC subsidy and with Indian Grant, respectively.